Design Thinking: An Alternative For Educational ICT Integration Training? - Alan Felix; Boitumelo Moreeng; Moeketsi Mosia (E-Journal of Humanities, Arts and Social Sciences, 2024)
Challenges to incorporating ICT in the classroom have been debated in various literature over the last few years. It is, therefore, important to seek different strategies to mitigate these challenges. Design thinking (DT) is considered an approach that can help improve teachers’ Technological Pedagogical and Content Knowledge (TPACK). This study therefore examined teachers’ experience when developing lessons using ICT using design thinking. This qualitative study was conducted in a primary school in South Africa. Data was collected from two social science (Geography) teachers using face-to-face interviews. Highlights from the study point to the following benefits namely, teachers can learn in collaboration, they can be supported by their peers, and they take part in high-order thinking practices to solve problems related to ICT integration. Therefore, it is recommended that a design thinking approach needs to be applied when teacher training workshops for ICT integration are offered. This study contributes to the existing literature on developing strategies to incorporate ICT in the curriculum of primary schools in South Africa.